2013
DOI: 10.2460/javma.243.8.1170
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of doxycycline in the tears and plasma of northern elephant seals (Mirounga angustirostris) following oral drug administration

Abstract: Objective-To assess tear and plasma concentrations of doxycycline following oral administration to northern elephant seals (Mirounga angustirostris). Design-Pharmacokinetic study. Animals-18 juvenile northern elephant seals without signs of ocular disease. Procedures-Study seals were receiving no medications other than a multivitamin and were free from signs of ocular disease as assessed by an ophthalmic examination. Doxycycline (10 or 20 mg/kg [4.5 or 9.1 mg/lb]) was administered orally every 24 hours for 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…One objective of the NLME model approach is to identify the appropriate covariates affecting the PK properties of a subpopulation and to explain the intersubject and intrasubject variability in terms of these covariates, which is helpful to optimize the initial dosage regimen to meet the therapeutic window and safety criterion of a certain subpopulation of animals …”
Section: Application Of Meta‐analysis and Nlme Model In Veterinary Drugsmentioning
confidence: 99%
“…One objective of the NLME model approach is to identify the appropriate covariates affecting the PK properties of a subpopulation and to explain the intersubject and intrasubject variability in terms of these covariates, which is helpful to optimize the initial dosage regimen to meet the therapeutic window and safety criterion of a certain subpopulation of animals …”
Section: Application Of Meta‐analysis and Nlme Model In Veterinary Drugsmentioning
confidence: 99%
“…As was previously reported for doxycycline in the tear film of horses and elephant seals, there was significant variability between subjects (Fig. b) …”
Section: Discussionmentioning
confidence: 99%
“…The lacrimal gland and gland of the third eyelid are the biggest contributors of aqueous tears in dogs and horses . In the case of minocycline and doxycycline, it is thought that the increased lipophilicity of these compounds concentrates these molecules in secretory glands such as the lacrimal gland . Previous studies have identified the continuous release of drug into the tear film past its plasma half‐life due to this concentration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Although a variety of antibiotics are commonly used in pinniped species, information on pharmacokinetics of these drugs remains scarce, with only a handful of studies thus far published. 11,12,19,22 The Marine Mammal Center (TMMC) is a rehabilitation facility that cares for roughly 600 ill and injured marine mammals each year, approximately 60% of which are California sea lions (Zalophus californianus). Ciprofloxacin is currently one of the most frequently administered antibiotics at TMMC, and is commonly used for treatment of California sea lions affected by a variety of bacterial infections, including pneumonia, leptospirosis, and infected traumatic injuries, at a dosage of 5-10 mg/kg p.o.…”
Section: Introductionmentioning
confidence: 99%